2014
DOI: 10.1111/eje.12110
|View full text |Cite
|
Sign up to set email alerts
|

Does Special Care Dentistry undergraduate teaching improve dental student attitudes towards people with disabilities?

Abstract: Dental students in our study had neither particularly positive, or negative attitudes towards people with disabilities. There was no statistically significant difference in student attitudes before and after the educational intervention. This study, therefore, shows that a comprehensive undergraduate blended learning module, which aimed to improve attitudes towards people with disabilities, did not do so, using the described measures within the selected timeframe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 32 publications
(66 reference statements)
2
43
2
1
Order By: Relevance
“…The dental procedures reported in the aforementioned studies also highlighted the treatment needs of the population. In people with disabilities, the simplest procedures can be difficult to perform due to problems associated with communication or physical constraints such as muscle stiffness, poor mouth opening, and resistance to treatment that often led to care under general anesthesia [ 85 ]. Four of the selected studies reported emergency treatment procedures [ 70 , 74 , 77 , 81 ]; dental extractions and other types of surgeries [ 71 , 76 , 78 , 80 83 ] and preventive procedures such as prophylaxis, sealants, and fluoride application were also reported [ 70 , 71 , 76 – 78 , 80 , 82 , 83 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dental procedures reported in the aforementioned studies also highlighted the treatment needs of the population. In people with disabilities, the simplest procedures can be difficult to perform due to problems associated with communication or physical constraints such as muscle stiffness, poor mouth opening, and resistance to treatment that often led to care under general anesthesia [ 85 ]. Four of the selected studies reported emergency treatment procedures [ 70 , 74 , 77 , 81 ]; dental extractions and other types of surgeries [ 71 , 76 , 78 , 80 83 ] and preventive procedures such as prophylaxis, sealants, and fluoride application were also reported [ 70 , 71 , 76 – 78 , 80 , 82 , 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…As this population needs specially organized health services and comprehensive preparation of professionals [85], it was observed that barriers to access were clearly pointed and appeared in all the included articles. However, there was no mention of the facilitators of access in any of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses and physiotherapists are essential health professionals in the multidisciplinary team as they have direct contact with the patients [ 11 ]. Moreover, the personal experience of the students of these disciplines will condition their attitude towards the patients [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, at the University of Michigan School of Dentistry, no positive changes in dental students’ attitudes toward community service after a community‐based educational experience were found . Similarly, a study in Dublin found that a brief comprehensive blended learning module, which aimed to improve the ATDP (Attitude Towards Disabled Persons Scale) of dental students, was not successful …”
Section: Discussionmentioning
confidence: 99%
“…19 Similarly, a study in Dublin found that a brief comprehensive blended learning module, which aimed to improve the ATDP (Attitude Towards Disabled Persons Scale) of dental students, was not successful. 20 Recently, the need to educate socially accountable dentists with the ability to take up a leading role in changing the system to address oral health inequities was argued. 21 Based on the experiences at Ghent University, the following guidelines to implement community service learning can be proposed:…”
Section: Discussionmentioning
confidence: 99%